Механізм управління стратегіями випереджаючого науково-технологічного інноваційного розвитку промислового підприємства - Ілляшенко, Наталія Сергіївна (My University, 2020)
У статті розроблено методологічні засади організаційно-економічного механізму управління стратегіями випереджаючого інноваційного розвитку промислового підприємства. Визначено принципи його формування і функціонування, окреслено склад підсистем механізму і їх елементів, розроблено методи і інструменти реалізації його функцій. Визначено порядок процедур реалізації функцій зазначеного механізму який відповідає розробленій автором системній карті стратегічного управління підприємством. Він передбачає послідовне застосування виділених у системній карті підходів до стратегічного управління, що доводить наукову обґрунтованість засадничих аспектів розробленого організаційно-економічного механізму. Окреслено основні складові успіху промислового підприємства-інноватора, обґрунтовано, що результативність впливу на них визначає ефективність управління стратегіями випереджаючого інноваційного розвитку. Розроблено концептуальну модель управління стратегіями випереджаючого науково-технологічного розвитку промислових підприємств. ЇЇ практична реалізація надасть принципову можливість цілеспрямовано управляти формуванням і впровадженням стратегій інноваційного розвитку промислових підприємств, що орієнтовані на "технологічний прорив" і виведення на ринок "підривних" інноваційних продуктів (виробів чи послуг).

The methodological foundations of organizational and economic mechanism for managing the strategies of leading innovative development of an industrial enterprise are developed in the article. The principles of its formation and functioning are determined. Top-level principles include those that are fundamental to leading the way: orientation to innovative development; the radical nature of innovative developments; continuity (cyclicality) of creation and introduction of innovations and struggle for leadership / its retention; prediction / formation of tendencies of scientific and technological development of the branch of the enterprise and related industries; knowledge orientation as a source of innovative developments; orientation to the quality of staff. The composition of the subsystems of the mechanism and their elements is outlined, methods and tools of its functions realization are developed. The procedure for implementing the functions of the specified mechanism, which corresponds to the system map developed by the author of strategic enterprise management, has been determined. It envisages the consistent application of strategic management approaches highlighted in the system map, which proves the scientific validity of the fundamental aspects of the developed organizational and economic mechanism. The author substantiates that the efficiency of functioning of organizational and economic mechanism of management of strategies of leading innovative development of industrial enterprises is determined by the effectiveness of managerial influences on the main components of success of innovative activity of a particular industrial enterprise. The author defines their composition as follows: management system, knowledge of the enterprise, staff, innovative culture, research and development, marketing of innovations, production, material resources. The conceptual model of management of the strategies of leading scientific and technological development of industrial enterprises is developed. Its practical implementation will give a principled opportunity to purposefully manage the formation and implementation of strategies for innovative development of industrial enterprises, focused on "technological breakthrough" and the launch of "disruptive" innovative products (products or services).
The mechanism of management of strategies for advancing scientific and technological innovation development of industrial enterprise
Keywords: економіка; маркетинг знань; інноваційна діяльність; трендвотчінг; персонал; матеріальні ресурси; виробництво; mechanism; advancing development; strategy management; innovation